Water and Poverty: A Case of Watershed Development in Andhra Pradesh, India - Reddy, V. Ratna; Reddy, Y. V. Malla; Soussan, John; Frans, Dirk (Water Nepal, 2004)
This case study of an inland and drought-prone district of Andhra Pradesh (AP) typifies the potential for and the challenges to poverty-focused watershed development in a semi-arid, low-resource and high-risk environment. These are the conditions under which much of the agricultural growth and poverty alleviation in India will have to take place in the future. In AP, the government’s watershed-related policies and programmes are implemented enthusiastically. The state is in the forefront as far as India’s watershed development programme is concerned and has so far implemented it in about 9,000 watersheds covering above three million hectares. This accounts for roughly a third of the land that needs treatment and a fifth of the total rain-fed area in the state. All watersheds, even though they fall under different schemes, are being treated as per the guidelines of the 1994-95 Watershed Development Committee. About 85 per cent of the watersheds are implemented through the government system, NGOs execute the rest. Studies show that the participatory approach used by NGOs has better economic and ecological impacts, a more equal spread of benefits and greater sustainability than the government approach. This case study, which is based on some of the successful NGO run watersheds, highlights that watershed development is a necessary but not sufficient condition for poverty alleviation in arid and semi-arid regions. It was observed that the impact of watershed development is significant where that development has led to improve water availability. The study identified some of the programmes that need to complement watershed development if it is to be an effective pro-poor programme. It underscores that poverty-focused policy interventions are crucial for maximising the overall accomplishment and poverty reduction impact of watershed development.Water Nepal Vol.11(1) 2004 pp51-73